ANALISIS FORECASTING (PERAMALAN) PRODUK KERIPIK PISANG KEMASAN BUNGKUS (STUDI KASUS : HOME INDUSTRY-KERIPIK PISANG SURAKARTA) - Erna Indriastiningsih; Anita Oktaviana Trisna Devi (Universitas Sahid Surakarta, 2016)
Forecasting is a method for estimating a value in the future by using past data. This research was conducted at the Home Industry Arwana Food. In this study, theauthor discusses the forecasting analysis of sales of banana chips products for packaging types. Forecasting is done using three methods, namely the Moving Averagemethod, the Exponential Smoothing with Trend method and the Trend analysis method by comparing the smallest error rate, the chosen forecasting method is the TrendAnalysis method, with the MAD value of 161.3539, MSE of 55744 , 16, and a standard error of 242,947. From the analysis of data processing that has been carried out basedon the chosen forecasting method, sales forecasting for banana chips products of packaged type is 1121,424 or 1122 packs / month, meaning that Home Industry -Surakarta Banana Chips must provide as many as banana chips. 1122 packs for each month.